2003
DOI: 10.1175/2761.1
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variability of the Western North Pacific Summer Monsoon: Differences between ENSO and Non-ENSO Years

Abstract: The interannual variability of the western North Pacific (WNP) summer monsoon is examined for the non-ENSO, ENSO developing, and ENSO decaying years, respectively. The ENSO developing (decaying) year is defined as the year before (after) the mature phase of ENSO, and the non-ENSO year is defined as the year that is neither the ENSO developing year nor the ENSO decaying year. A strong (weak) WNP summer monsoon tends to occur during the El Niño (La Niña) developing year and a weak (strong) WNP summer monsoon ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 49 publications
(27 reference statements)
8
74
1
Order By: Relevance
“…The post-Changma mode indicated the decaying phase of the La Niña. This was the same result as that obtained by Chou et al (2003), who showed that a strong WNPSM tended to occur in the decaying year of the La Niña. The dry-spell mode was also observed to be related with the La Niña events.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The post-Changma mode indicated the decaying phase of the La Niña. This was the same result as that obtained by Chou et al (2003), who showed that a strong WNPSM tended to occur in the decaying year of the La Niña. The dry-spell mode was also observed to be related with the La Niña events.…”
Section: Discussionsupporting
confidence: 90%
“…Lee et al (2013b) indicated that the moisture convergence is simultaneously enhanced by inducing impact of more evaporation through anomalous SST warming over the IO. The moisture supply over East Asia is also related to external forcing such as the ENSO through the modulation of an anomalous WNPSH (Huang and Wu 1989;Wang et al 2000Wang et al , 2013Chou et al 2003;Lee et al 2013a;Yun et al 2013). The anomalous WNPSH is attributed to local air-sea interactions, the influence of the IO, and the combined effect on atmospheric circulation (Ashok et al 2001;Saji and Yamagata 2003;Xie et al 2009;Lee et al 2013b;Yun et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…All the three largest El Niño Modoki events during our data period did not occur in the summer ''after'' the mature phase of a cold ENSO. This fact further elucidates that the intensities of the western North Pacific summer monsoon and the East Asian summer monsoon do not have a simple relation with the phase of the warm-cold ENSO cycle (Chou et al 2003). It further shows that El Niño Modoki is not necessarily one stage of the ENSO cycle, so that the influence of El Niño Modoki on these monsoons should not be mixed up with that of El Niño.…”
Section: Hpa Wind and Related Rainfallmentioning
confidence: 83%
“…Advances in remote sensing have provided us with long-term and globally complete satellite-gauge-merged precipitation products and satellite-based estimates, such as the Global Precipitation Climatology Project (GPCP) [8], the Climate Prediction Center Merged Analysis of Precipitation (CMAP) [9], and the Tropical Rainfall Measuring Mission (TRMM) Multi-satellite Precipitation Analysis (TMPA) [10]. Many studies have investigated the impacts of ENSO on precipitation using these satellite-based precipitation datasets [11][12][13][14][15][16]. For example, Dai and Wigley [11] and Haddad et al [14] derived the global climatology and variability of ENSO-induced precipitation using the CMAP and TRMM datasets, respectively, and found that ENSO is the major driver of the interannual variability of global rainfall.…”
Section: Introductionmentioning
confidence: 99%